The Impact of Local Governments’ Social Transfers on Poverty Reduction In Indonesia - Bayu Kharisma*; Sutyastie S. Remi; Muhammad Syaiful; Ricky Abdillah (LPPM Universitas BSI, 2020)
ABSTRACT This research aims to examine the impact of intervention to poverty reduction, manifested through social transfers from local governments’ budget (APBD). We use provincial panel data to examine the extent of impact from such transfer to poverty alleviation performance. Using Beck and Katz’s OLS-PCSE estimator, we confirmed that higher amount of social transfer is indeed beneficial for further reduction in poverty incidence. Other explanatory variables, namely GDP per capita and human capital, also demonstrate significant effects in decreasing the number of poor people, while higher unemployment can lead to addition of the number of people living below the poverty line. These findings suggest that the declining trend in social transfers channelled by local governments might underlie the stagnation of poverty reduction in the last decades. We therefore suggest that ensuring the sustainability of transfers to the poor from local governments’ funds is very important to re-accelerate poverty reduction.Keywords: social transfer; local government; poverty reduction; OLS-PCSE estimator